Comprehensive Understanding of the Endogenous Regulation of Seasonal Reproduction - Arora, Sweta; Basu, Priyoneel; Kanhar, Janhiphula; Naik, Prakasini; Meher, Mantu (Contemporary Research and Perspectives in Biological Science Vol. 10, 2025)
This paper provides a comprehensive overview of the endogenous regulation of seasonal reproduction in animals, highlighting the intricate relationship between environmental conditions and the endocrine system. It discusses how animals adapt their reproductive cycles in response to changes in external factors such as temperature, daylight, and food availability. Central to this process is the hypothalamic-pituitary-gonadal (HPG) axis, a complex neuroendocrine system comprising the hypothalamus, pituitary gland, and gonads, which work together to regulate reproductive functions. Key components involved in this regulation include gonadotropin-releasing hormone (GnRH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), and various hormones and neurochemicals such as melatonin, glucocorticoids, kisspeptin, and leptin. Their roles in modulating the reproductive cycle are detailed throughout this study. The importance of melatonin is particularly emphasized, as it converts photoperiodic information into hormonal signals that influence reproductive timing in seasonally breeding mammals. This review considers both pioneering experiments and more recent studies, underscoring the complexity of hormonal interactions in reproductive regulation and the adaptive mechanisms that animals employ in response to changing environmental cues.